2018
DOI: 10.1111/tpj.13914
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin‐dependent kinase G group defines a thermo‐sensitive alternative splicing circuit modulating the expression of ArabidopsisATU2AF65A

Abstract: SummaryThe ability to adapt growth and development to temperature variations is crucial to generate plant varieties resilient to predicted temperature changes. However, the mechanisms underlying plant response to progressive increases in temperature have just started to be elucidated. Here, we report that the cyclin‐dependent kinase G1 (CDKG1) is a central element in a thermo‐sensitive mRNA splicing cascade that transduces changes in ambient temperature into differential expression of the fundamental spliceoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 85 publications
3
52
1
7
Order By: Relevance
“…The wild type Columbia (Col-0) and mutant stocks cdkg1-1 (SALK_075762), cdkg2-1 (SALK_012428), and cycL1-1 (SAIL_285_G10) used in this study were obtained from the Nottingham Arabidopsis Stock Centre and have previously been described (Zheng et al, 2014;Ma et al, 2015;Cavallari et al, 2018).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wild type Columbia (Col-0) and mutant stocks cdkg1-1 (SALK_075762), cdkg2-1 (SALK_012428), and cycL1-1 (SAIL_285_G10) used in this study were obtained from the Nottingham Arabidopsis Stock Centre and have previously been described (Zheng et al, 2014;Ma et al, 2015;Cavallari et al, 2018).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…CDKC, for instance is part of the positive transcription elongation factor b (P-TEFb) that phosphorylates the C-terminal domain of RNA polymerase II (PolII) (Cui et al, 2007), modulates the localization of spliceosome components (Kitsios et al, 2008) and can regulates flowering time through promoting expression of an FLC antisense transcript called COOLAIR (Wang et al, 2014). The CDKG group is the most closely related to mammalian CDKs (Menges et al, 2005;Umeda, 2005) that are involved in mRNA processing (Bartkowiak et al, 2010;Chen et al, 2006;Loyer et al, 2005;Even et al, 2006) and have been also shown to regulate splicing (Huang et al, 2013;Cavallari et al, 2018), meiosis (Zheng et al, 2014) and flowering responses (Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its meiotic role, it is clear that CDKG1 also has wider functions including the role in promoting somatic DNA repair by homologous recombination described here. Moreover, CDKG1 affects splicing in somatic tissues (Cavallari et al, 2018), and in anthers, the loss of CDKG1 results in the incorrect splicing of the callose synthase gene CalS5, impaired callose synthesis and abnormal pollen cell wall formation (Huang et al, 2013). This likely contributes to the low seed set observed in cdkg1-1 mutants, despite a relatively modest reduction in bivalent number.…”
Section: A Model For the Role Of Cdkg1 During Male Meiosismentioning
confidence: 99%
“…Finally, CDKG1 was also found-like other major genes regulating recombination, such as FANCMto play an important role in somatic DNA repair. Other studies have found that CDKG1 is involved in temperaturespecific splicing cascades (Cavallari et al, 2018), stimulating speculation regarding the possible mechanism by which it may act. Thus, further work on the molecular mechanisms by which CDKG1 regulates meiotic proteins might reveal additional facets of an important protein.…”
mentioning
confidence: 99%